Formulasi etnomatematika pada konsep operasi penjumlahan dalam permainan tradisional kemyeng di Kabupaten Indramayu (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The development of technology has more or less changed children. In ancient times, children played traditional games together in their spare time. However, at this time most children prefer to play online using gadgets rather than playing with their friends which can affect student learning outcomes. Therefore, there is a need for learning that links traditional games with mathematics lessons. The purpose of this study is to describe the mathematical concepts contained in the traditional game of kempyeng and to formulate ethnomathematics in the traditional game of kempyeng. This research is a qualitative research with an ethnographic approach. This research was conducted in the village of Terusan, Sindang District, Indramayu Regency. This game is played by four children who are still in elementary school as well as respondents in the interview process. Data was collected through observation, interview and documentation techniques. The instruments used are observation sheets, interview transcripts, and documentation tools. The results showed that there are concepts of arithmetic operations, namely addition and multiplication. The ethnomathematics contained in the kempyeng game is the addition and multiplication of ten based on the acquisition of the bottle cap captured by the player.
Keywords: ethnomathematics; traditional game kempyeng; arithmetic operation concept